New Early Cretaceous clam shrimps (Spinicaudata) from uppermost Bouhedma Formation of northern Chotts range, southern Tunisia: Taxonomy, stratigraphy and palaeoenvironmental implications. (April 2017) - Li, Gang; Boukhalfa, Kamel; Teng, Xiao; Soussi, Mohamed; Ben Ali, Walid; Ouaja, Mohamed; Houla, Yassine
Abstract: The fossil clam shrimp genus Ordosestheria was originally described from the Lower Cretaceous (Aptian) Jingchuan Formation in Inner Mongolia, northwestern China. The species taxonomically described in this paper as Ordosestheria chottsensis sp. nov. was recovered from the uppermost Bouhedma Formation in the northern Chotts range of southern Tunisia. The early Barremian occurrence of the genus in Tunisia suggests that ordosestheriids have most likely originated in North Africa and then migrated to East Asia in the Aptian. Moreover, the occurrence of fossil spinicaudatans in two horizons respectively from the Bouhedma and Sidi Aïch formations indicates the interaction of freshwater and marine conditions that characterized the northern African margin as part of widespread complex paralic environments over the Chotts and Gafsa areas during the Barremian. Highlights: New clam shrimps from uppermost Bouhedma Formation of Tunisia. New species of Ordosestheria is taxonomically described basing on SEM imaging. The early Barremian occurrence indicates ordosestheriids originated in North Africa.